Hypoglycemic and Lipidemic Effects of Irvingia gabonensis Seeds in Long-Evans Rats (Dhaka University Journal of Pharmaceutical Sciences, 2025)
The n-hexane extract and 80% ethanol extract of defatted residue (dfr) of Irvingia gabonensis (seeds) were evaluated for their hypoglycemic and hypolipidemic effects on the rats with type 2 Diabetes. In addition, GC analysis of nhexane extract was also investigated. A rat insulin ELISA kit was used to assess the serum insulin level. The measurements of total serum cholesterol and triglycerides (TG) were made using the enzymetic-colorimetric (cholesterol CHOD-PAP) method. The anthrone-reagent was used to measure liver glycogen level. The obtained results indicated that oral treatment of both extracts, 80% ethanol extract of dfr and n-hexane extract, significantly reduced serum glucose levels on the 14th day (p=0.000; p=0.001) and 21st day (p=0.001; p=0.000), respectively. The glucose level reduction was similar to that of the positive standard glibenclamide-treated group. The n-hexane extract significantly raised fasting serum insulin (p=0.02) but 80% ethanol extract of dfr showed no significant effect. 80% ethanol extract of dfr considerably raised serum HDL levels (p=0.004) and decreased serum TG levels (p=0.03). There were essentially the same effects were observed with nhexane extract. Neither LDL and serum cholesterol levels nor body weight showed any change over the course of the study. The glycemic and lipidemic state of type 2 diabetes model rats are found to be improved by n-hexane extract and 80% ethanol extract of dfr.Dhaka Univ. J. Pharm. Sci. 24(2): 131-138, 2025 (December)